2014
DOI: 10.3109/13880209.2014.941506
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoprotective effect of ethanol extract fromBerchemia lineateagainst CCl4-induced acute hepatotoxicity in mice

Abstract: Objective: The present study investigates the hepatoprotective effect of Berchemia lineate ethanol extract (BELE) on CCl 4 -induced acute liver damage in mice. Materials and methods: Effect of BELE administrated for 7 consecutive days was evaluated in mice by the serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), total bilirubin (TBIL), albulin (ALB), globulin (GLB), and total protein (TP) levels, as well as liver superoxide dismutase (SOD) activity and malondia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Also, CCl4 injected rats (group 3) showed an increase in ALP level. These result was agreed with Deb, (1998) and Li et al, (2015). Theses alterations may be attributed to the increase synthesis ALP due to the biliary tract involvement (Muriel et al, 1992).…”
Section: Disucssionsupporting
confidence: 91%
“…Also, CCl4 injected rats (group 3) showed an increase in ALP level. These result was agreed with Deb, (1998) and Li et al, (2015). Theses alterations may be attributed to the increase synthesis ALP due to the biliary tract involvement (Muriel et al, 1992).…”
Section: Disucssionsupporting
confidence: 91%
“…These findings were consistent with those of many previous studies that showed administration of several antioxidant mixtures significantly decreased the levels of serum marker enzymes relative to vehicle groups in CCl 4 treated animals. For example, the level of ALT, ALP, and AST was significantly decreased by methanol extract of Carissa opaca leaves (MCL) [ 43 ], aqueous leaf extract of Persea Americana (AEPA) [ 44 ], Berchemia lineate ethanol extract (BELE) [ 45 ], methanol extract of Melaleuca styphelioides (MSE) [ 46 ], and polyphenols-enriched extract from Huangshan Maofeng green tea (HMTP) [ 47 ]. However, MCL treatment induced a decrease in LDH level [ 43 ], which may have been caused by differences in the composition or concentration of bioactive compounds among studies.…”
Section: Discussionmentioning
confidence: 99%
“…CCl 4 injury mouse model. A CCl 4 -induced acute liver injury model of mice was established as described by Li et al (22). Male Kunming mice (20±2 g; n=60) were purchased from the Experimental Animal Center of Anhui Medical University [animal license no.…”
Section: Methodsmentioning
confidence: 99%